A review of policy drivers and barriers for the use of anaerobic digestion in Europe, the United States and Australia. (December 2015) - Edwards, Joel; Othman, Maazuza; Burn, Stewart
Abstract: Anaerobic digestion (AD) of biomass has become a common technology used in many European nations and is receiving increased attention in other nations. The chief attraction of AD is it generates renewable energy. Yet it also manages and treats organic waste, recycles key nutrients to soil, and can create local jobs; making AD an attractive technology to governments. In this paper we review the role government policy has played in promoting AD use and driving its growth in five developed nations studied; Australia, Denmark, Germany, the UK and USA. These nations were chosen for review as they provide a breadth of AD use with the number of AD plants in the aforementioned nations totaling 78, 114, 9545, 265, and 1497. This review looks to demonstrate and discuss policy mechanisms introduced by each nation that has helped drive AD use, and identify areas where policy can help overcome enduring challenges that face the AD industry. Focused discussion is given to waste management, climate change and energy security policies, and to financial incentives made available to AD installations. Analysis shows that the impact of performance based incentives targeted at small-medium capacity AD plants, less than 500 kW, have a significant positive correlation with the growth of AD use in the UK and Germany. The relatively new AD industry faces a number of barriers, which are also discussed, but with the help of supportive government policy for the technology, that considers the wide-ranging benefits of AD across government portfolios; investors will be more likely to show interest in the developing AD industry.